Analisis Minat Belajar Siswa terhadap Pembelajaran Daring pada Masa Pandemi COVID-19 di UPT SD Negeri 1 Lawawoi - muhammad asrul sultan; Rusda Riyani (Universitas Negeri Makassar, 2021)
This research is a descriptive study that objective to determine student interest in online learning during the COVID-19 pandemic at UPT SD Negeri 1 Lawawoi, Sidenreng Rappang Regency. The population in this study were all students of UPT SD Negeri 1 Lawawoi totaling 248 people while the sample in this study was class IV A, IV B, VA, VB, VI A, VI B, which totals 118 people with a purposive sampling technique. The instrument in this research used a questionnaire. The data analysis technique used is a descriptive statistical analysis of quantitative data. Based on the results of descriptive analysis, the data obtained showed that student's interest in online learning during the COVID-19 pandemic at UPT SD Negeri 1 Lawawoi, Sidenreng Rappang Regency was in the moderate category with a percentage of 44,1%.